The effect of a cognitive training therapy based on stimulation of brain oscillations in patients with mild cognitive impairment in a Chilean sample: study protocol for a phase IIb, 2 × 3 mixed factorial, double-blind randomised controlled trial - FIGUEROA VARGAS, ALEJANDRA MABEL; Begoña Góngora; María Francisca Alonso; Alonso Ortega; Patricio Soto-Fernández; Lucía Z-Rivera; Sebastián Ramírez; Francisca González; MUÑOZ VENTURELLI, PAULA ANDREA; BILLEKE BOBADILLA, PABLO ERNESTO (My University, 2024)
Abstract Background The ageing population has increased the prevalence of disabling and high-cost diseases, such as dementia and mild cognitive impairment (MCI). The latter can be considered a prodromal phase of some dementias and a critical stage for interventions to postpone the impairment of functionality. Working memory (WM) is a pivotal cognitive function, representing the fundamental element of executive functions. This project proposes an intervention protocol to enhance WM in these users, combining cognitive training with transcranial electrical stimulation of alternating current (tACS). This technique has been suggested to enhance the neuronal plasticity needed for cognitive processes involving oscillatory patterns. WM stands to benefit significantly from this approach, given its well-defined electrophysiological oscillations. Therefore, tACS could potentially boost WM in patients with neurodegenerative diseases. Methods This study is a phase IIb randomised, double-blind clinical trial with a 3-month follow-up period. The study participants will be 62 participants diagnosed with MCI, aged over 60, from Valparaíso, Chile. Participants will receive an intervention combining twelve cognitive training sessions with tACS. Participants will receive either tACS or placebo stimulation in eight out of twelve training sessions. Sessions will occur twice weekly over 6 weeks. The primary outcomes will be electroencephalographic measurements through the prefrontal theta oscillatory activity, while the secondary effects will be cognitive assessments of WM. The participants will be evaluated before, immediately after, and 3 months after the end of the intervention. Discussion The outcomes of this trial will add empirical evidence about the benefits and feasibility of an intervention that combines cognitive training with non-invasive brain stimulation. The objective is to contribute tools for optimal cognitive treatment in patients with MCI. To enhance WM capacity, postpone the impairment of functionality, and obtain a better quality of life. Trial registration ClinicalTrials.gov NCT05291208. Registered on 28 February 2022. ISRCTN87597719 retrospectively registered on 15 September 2023.
Keywords: mild cognitive impairment; cognitive training; working memory; cognitive functions; non-invasive brain stimulation; randomised controlled trial